2017
DOI: 10.1177/0042085917714516
|View full text |Cite
|
Sign up to set email alerts
|

“That’s Why I Say Stay in School”: Black Mothers’ Parental Involvement, Cultural Wealth, and Exclusion in Their Son’s Schooling

Abstract: This study examines parental involvement practices, the cultural wealth, and school experiences of poor and working-class mothers of Black boys. Drawing upon data from an ethnographic study, we examine qualitative interviews with four Black mothers. Using critical race theory and cultural wealth frameworks, we explore the mothers’ approaches to supporting their sons’ education. We also describe how the mothers and their sons experienced exclusion from the school, and how this exclusion limited the mothers’ inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 75 publications
2
56
0
Order By: Relevance
“…Studies of parents' school engagement tend to focus predominantly on mothers and, specifically, heterosexual mothers (Allen & White‐Smith, 2017; Nomaguchi & Milkie, 2020). Studies that do include fathers tend to focus on heterosexual fathers (Jeynes, 2007; Lareau, 2003; McBride, Schoppe‐Sullivan, & Ho, 2005) and often fail to disaggregate mothers' and fathers' involvement, or focus exclusively on mothers (Muller, 1995; Ream & Palardy, 2008; Turney & Kao, 2009).…”
Section: School Engagement and Parent Communitiesmentioning
confidence: 99%
“…Studies of parents' school engagement tend to focus predominantly on mothers and, specifically, heterosexual mothers (Allen & White‐Smith, 2017; Nomaguchi & Milkie, 2020). Studies that do include fathers tend to focus on heterosexual fathers (Jeynes, 2007; Lareau, 2003; McBride, Schoppe‐Sullivan, & Ho, 2005) and often fail to disaggregate mothers' and fathers' involvement, or focus exclusively on mothers (Muller, 1995; Ream & Palardy, 2008; Turney & Kao, 2009).…”
Section: School Engagement and Parent Communitiesmentioning
confidence: 99%
“…Outside of mediated context, scholars also apply CCW examining its influence on Black communities. This work uncovers significant benefits that contribute to the racial and gendered group’s various forms of acquired cultural capital within spaces that often have a history of oppression or exclusion of Black bodies (Allen & White-Smith, 2018; Burt & Johnson, 2018; Cooper et al., 2017; Jayakumar et al., 2013). For instance, Burt and Johnson (2018) found that interpersonal support and mentorship aided Black men in building aspirational capital in their pursuit of science, technology, engineering, mathematics education.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…Historically, possessing navigational capital infers the ability to maneuver through institutions, including educational institutions, vocational spaces, and social systems. People of color rely on various social and psychological navigational skills to function among structures that uphold inequality and are permeated by “isms,” which may promote social stigmas and microaggressions (Allen & White-Smith, 2018; Cooper et al., 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Over 80% of African American parents use racial socialization, with two modes being especially prominent: cultural socialization-promoting knowledge of positive racial histories and feelings of racial pride-and bias socializationteaching awareness and coping strategies related to racial discrimination experiences (Hughes et al, 2006;Huguley et al, 2019). Studies in educational contexts specifically have noted that discrimination experiences are common in schools (Allen, 2012;Carter Andrews & Gutwein, 2017;Howard & Reynolds, 2008;Wang & Huguley, 2012) and that in response, African American parents use racialized educational messages to promote resistance, resilience, and overall achievement in the face of these encounters (Allen & White-Smith, 2018;Carter Andrews, 2012;Scott et al, 2019;Yosso, 2005). Considered in tandem, racial socialization and the integrative developmental model elucidate both how and why families of color in inhibiting environments work to mitigate the psychological and material costs of racial subordination on their children's educational prospects.…”
Section: Theoretical Frameworkmentioning
confidence: 99%